Potential and Transformation of Indigenous Floral Foods in Africa: What Research Tells Over the Past Two Decades (2000–2022) - Achoja Roland Onomu; Amon Taruvinga; Willie Tafadzwa Chinyamurindi (Advances in Agriculture)
Indigenous foods are the ancestral diet endemic to and consumed by the local people for ages, but there has been a recent discrepancy in their acceptability, growth and development. While some research suggested frequent consumption and growth of indigenous foods, others reported poor development and declining consumption despite their rich nutrition content. Moreover, research has failed to investigate and compile indigenous foods’ growth and developmental trends in whole and niche areas to ensure their promotion and competitiveness with their exotic counterparts due to reports highlighting their rambling and anecdotal pictures of economic significance and nutritional potential. The study reviewed literature and collated past research to examine and forecast the developmental growth of indigenous foods for more than two decades (2000–2022). It identifies niche areas that have received more or less growth of indigenous food, and the type of research (review, data, and experimental research) contributing to its growth and development. Through the review of related literature, this study demonstrates that indigenous foods contribute to improving household health, food, and nutritional security. For example, 80% of South Africans depend on indigenous foods for medicinal purposes. It also enhances the dietary diversity of household and reduces poverty through income generation and employment. Some indigenous foods (green leafy vegetables) are richer sources of mineral elements than their exotic crops counterparts. Some indigenous foods play a crucial role in the cultural identity of people/ethnic groups. Indigenous foods are beneficial in terms of income, as research shows that some households generate more than 25% of their income from the sales of indigenous foods harvested from the wild. Indigenous foods agribusiness is dominated by rural dwellers, the poor, and vulnerable people, with most (75%) of the stakeholders being elderly women. Most indigenous foods transactions occur in an open market structure and are overshadowed by vendors and middlemen. 951 articles were used to investigate the growth show steady growth and development of indigenous foods research. However, the growth is skewed toward a few niche areas. Medicinal, food, and nutritional composition analysis are some niche areas witnessing indigenous foods’ rapid growth and research development. Some indigenous foods have also seen growth in research development in a domestication niche area, but growth and development are lacking in the genetic improvement of many indigenous foods. Lack of awareness campaigns, value addition, marketing, and private/entrepreneurial investment and managerial/logistic techniques are other niche areas slowing the growth of indigenous foods, as revealed by the limited research. In decades (2000–2022), only 5.99% and 3.79% of research focused on indigenous foods value addition and awareness campaigns. More pragmatic research, policies, promotions, and value-additions approaches are needed.